2010
DOI: 10.1002/da.20741
|View full text |Cite
|
Sign up to set email alerts
|

A review of empirically supported psychological therapies for mood disorders in adults

Abstract: Background-The mood disorders are prevalent and problematic. We review randomized controlled psychotherapy trials to find those that are empirically supported with respect to acute symptom reduction and the prevention of subsequent relapse and recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(165 citation statements)
references
References 204 publications
(425 reference statements)
1
153
0
11
Order By: Relevance
“…Furthermore, research in the past two decades has taught us that psychotherapeutic treatments of depression are superior to waitlist and other control conditions (Barth et al 2013;Lambert, 2013), and that psychotherapy combined with anti-depressant medication is more effective than medication alone (Barber et al 2013;Köhler et al 2013;Hollon et al 2014;Fonagy, 2015;Leichsenring et al 2015). There is also evidence suggesting that some types of psychotherapies are not only as effective as medication, but also have higher long-term enduring effects (Hollon & Ponniah, 2010;Cuijpers et al 2013b). We begin by briefly reviewing some of the major findings that have arisen from the literature on treatments of depression, focusing only on the best-known and more widely researched.…”
Section: What Do We Know About the Efficacy Of Psychotherapies For Dementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research in the past two decades has taught us that psychotherapeutic treatments of depression are superior to waitlist and other control conditions (Barth et al 2013;Lambert, 2013), and that psychotherapy combined with anti-depressant medication is more effective than medication alone (Barber et al 2013;Köhler et al 2013;Hollon et al 2014;Fonagy, 2015;Leichsenring et al 2015). There is also evidence suggesting that some types of psychotherapies are not only as effective as medication, but also have higher long-term enduring effects (Hollon & Ponniah, 2010;Cuijpers et al 2013b). We begin by briefly reviewing some of the major findings that have arisen from the literature on treatments of depression, focusing only on the best-known and more widely researched.…”
Section: What Do We Know About the Efficacy Of Psychotherapies For Dementioning
confidence: 99%
“…Some researchers found that different psychotherapies are effective in preventing relapse/recurrence Hollon & Ponniah, 2010;Steinert et al 2014;Biesheuvel-Leliefeld et al 2015) and that their enduring effects are as effective as a continuous use of medications (Cuijpers et al 2013b). In contrast, others have shown that the superiority of EBT for acute depression and anxiety disorders over TAU is minimal on 0-4-month follow-ups, and does not extend at 8-12-month follow-ups (Flückiger et al 2014).…”
Section: Enduring Effects Of Psychotherapymentioning
confidence: 99%
“…These findings focused current efforts for improving psychosocial functioning in BD on reducing subsyndromal depressive symptoms (M. Bauer et al, 2009) and cognitive dysfunction (Bearden et al, 2011;Deckersbach et al, 2010;Martínez-Arán et al, 2011), as well as enhancing stress management and interpersonal skills (Frank et al, 2000;Martínez-Arán et al, 2011). The bulk of this research emphasizes pharmacological interventions (Nivoli et al, 2011), followed by psychosocial treatments, such as psychotherapy (Ball et al, 2006;Hollon & Ponniah, 2010;Miklowitz, George, Richards, Simoneau, & Suddath, 2003;Miklowitz et al, 2008) and psychoeducation (Colom et al, 2009), as well as cognitive (Deckersbach et al, 2010) and functional remediation (Martínez-Arán et al, 2011). More broadly, the current overall approach to improving psychosocial adjustment in BD focuses on changing internal factors, with less consideration given to reducing environmental barriers to functioning.…”
Section: Predictors Of Psychosocial Functioning In Bdmentioning
confidence: 99%
“…En los últimos 20 años, se han desarrollado y validado un importante número de tratamientos cognitivo-conductuales basados en la evidencia (Hollon, y Ponniah, 2010;Nathan, y Gorman, 2007;Norton, y Price, 2007;Olatunji, Cisler, y Deacon, 2010). Sin embargo, se trata de protocolos de tratamiento específicos, cada uno de ellos orientado al tratamiento de un determinado trastorno psicológico.…”
Section: Introductionunclassified